1981
DOI: 10.1159/000232736
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Adjuvant-Independent IgE Responses in Inbred Mice: Primary, Secondary, and Persistent IgE Responses to Ovalbumin and Ovomucoid

Abstract: Immunization of a number of inbred mouse strains inraperitoneally with low levels (1–100 µg) of ovalbumin (OA) or ovomucoid (OM) in the absence of adjuvant, revealed marked strain differences in IgE responsiveness. High-OA-responder strains such as Balb/c exhibited PCA titres up to 256 in the primary response, and up to 1,280 in the secondary, while non-responders such as SJL and NZB remained PCA negative; similar variations were found in the response of the strains to OM. Repeated immunization of high-OA-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 1 publication
7
55
0
Order By: Relevance
“…Vaz et al (16) demonstrated that H-2b, H-2d and H-2q are linked to high IgE responsiveness to OA and to low responsiveness to OM in different strains of mice given low-dose antigen intraperitoneally with alum adjuvant. Holt et al (4) showed data different from those of Vaz et al in mice given low-dose antigen intraperitoneally without adjuvant. Further work will be required to confirm the specificity of genetically controlled responsiveness to Japanese cedar pollen.…”
Section: Discussionmentioning
confidence: 81%
“…Vaz et al (16) demonstrated that H-2b, H-2d and H-2q are linked to high IgE responsiveness to OA and to low responsiveness to OM in different strains of mice given low-dose antigen intraperitoneally with alum adjuvant. Holt et al (4) showed data different from those of Vaz et al in mice given low-dose antigen intraperitoneally without adjuvant. Further work will be required to confirm the specificity of genetically controlled responsiveness to Japanese cedar pollen.…”
Section: Discussionmentioning
confidence: 81%
“…Thirty min later the rats were euthanized and OVA-specifi c IgE titers were measured. The highest serum dilution giving a 5-mm diameter fl are or bluing reaction was taken as the PCA titer (Holt et al, 1981).…”
Section: Determination Of Ova-specifi C Antibody By the Pca Testmentioning
confidence: 99%
“…While IgE production can be induced in mice (13)(14)(15)(16)(17)(18)(19), especially after immunization that includes use of an adjuvant (18,19), we have elected to sensitize mice through inhalation of allergen without use of adjuvants. This bypasses problems raised by the observations that adjuvants themselves may induce nonspecific T cell and other inflammatory responses, as well as affect several cellular functions (20,21).…”
Section: Introductionmentioning
confidence: 99%